Aristotle on Household, Polis and Regime - Metheechutikul, Chutidech (Journal of Letters, 2025)
This article studies the work of Aristotle, Politics, to indicate the relationship among household, polis and regime. The article finds that, the article finds that polis links to the idea of household in the sense that household can represent the status of the polis in terms of wealth and the question of is the regime a good one? For this, household, polis and regime are related like a chain regarding how the smallest unit affects the bigger units which mean house, village, city, and then polis. On the other hand, household can be good or not, depending on how the regime can respond to the needs including survival, security, property and materials pursuance for managing household, and the pursuit of happiness.